Intelligent Patient Management - McClean, Sally (Springer, 2017)
Arguably medicine is either an arts-based science or a science-based art. In medieval times, clinical decisions were based on simple measures, such as the temperature of the body, the rhythm of the pulse, the consistency of the stool and the colour of the urine. Nowadays, thanks partly to modern technology, medical science has improved in many ways, as has healthcare. In particular, approaches which have their origins in Artificial Intelligence and Operational Research have a significant contribution to make in terms of improving not only diagnosis and treatment of patients, but also providing ways of managing patients in a more effective, more efficient, and more patient-friendly manner. This book focuses on the use of such Intelligent Patient Management to the benefit of clinicians, other healthcare and community practitioners and managers, patients and carers.